Participation of Australian Aboriginal and Torres Strait Islander families in a parent support programme: longitudinal associations between playgroup attendance and child, parent and community outcomes. (13th October 2016) - Williams, K. E.; Berthelsen, D.; Viviani, M.; Nicholson, J. M.
Abstract: Background: Playgroups are a relatively unique form of family support programme that is common in Australia which has high community acceptance and significant government investment. However, limited evidence exists regarding the effectiveness of playgroups to achieve better outcomes for children and their parents. This study describes patterns of playgroup participation for Aboriginal and Torres Strait Islander families with young children and examines the extent to which participation from birth to three years is associated with subsequent child, parent and community outcomes. Methods: This study uses three years of longitudinal data for 622 Aboriginal and Torres Strait Islander children who were participants in the Longitudinal Study of Indigenous Children (LSIC). Longitudinal associations between playgroup attendance when children were age 2 and 3 years and outcome measures for child vocabulary, motor skills, behaviour problems, prosocial development, parent home learning engagement, resilience, advice‐seeking and health service use, and community trustworthiness were examined using path analysis. Results: Rates of playgroup participation in this sample group were generally lower than for Australian children overall. Playgroup attendance when children were age 2 to 3 years was associated with higher parental engagement in home learning activities when children were aged 4 years which, in turn, was associated with stronger expressive vocabulary scores for children. Conclusion: The findings from this study suggest that playgroup participation can enhance the home learning environments for Aboriginal and Torres Strait Islander children. Playgroups as a parent support programme hold strong potential to reach and engage families, particularly in areas of high geographic isolation, which can realize improved outcomes for children, parents and communities.